Enhancement of accelerated carbonation of alkaline waste residues by ultrasound. (April 2016) - Araizi, Paris K.; Hills, Colin D.; Maries, Alan; Gunning, Peter J.; Wray, David S.
Highlights: Sonication increased the CO2 uptake of high w/s ratio samples by up to 400%. Sonication increased the CO2 uptake of low w/s ratio samples by up to 28%. The concentration of calcite increased during sonication. Upon sonication the particle size ( d (0.5)) decreased. Abstract: The continuous growth of anthropogenic CO2 emissions into the atmosphere and the disposal of hazardous wastes into landfills present serious economic and environmental issues. Reaction of CO2 with alkaline residues or cementitius materials, known as accelerated carbonation, occurs rapidly under ambient temperature and pressure and is a proven and effective process of sequestering the gas. Moreover, further improvement of the reaction efficiency would increase the amount of CO2 that could be permanently sequestered into solid products. This paper examines the potential of enhancing the accelerated carbonation of air pollution control residues, cement bypass dust and ladle slag by applying ultrasound at various water-to-solid (w/s) ratios. Experimental results showed that application of ultrasound increased the CO2 uptake by up to four times at high w/s ratios, whereas the reactivity at low water content showed little change compared with controls. Upon sonication, the particle size of the waste residues decreased and the amount of calcite precipitates increased. Finally, the sonicated particles exhibited a rounded morphology when observed by scanning electron microscopy.